1999
DOI: 10.1038/sj.bjp.0702696
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the muscarinic receptor in isolated uterus of sham operated and ovariectomized rats

Abstract: 1 The pharmacological characteristics of muscarinic receptors in rat isolated uterus were studied in ovariectomized (ov.) and sham operated (sh.) animals. 2 Competition radioligand binding studies, using uterine membranes and [ 3 H]-NMS, were undertaken with several muscarinic receptor antagonists. Most of the antagonists indicated a onesite ®t with apparent a nity estimates (pK i ) unchanged by ovariectomy. The selective M 2 antagonist, tripitramine revealed high (representing 33+8 and 38+2%) and low (67+8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…11). This finding is consistent with studies on nonvascular smooth muscles that indicate contraction is mediated predominantly via M 3 receptor stimulation (1,9,10,18,23,38).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…11). This finding is consistent with studies on nonvascular smooth muscles that indicate contraction is mediated predominantly via M 3 receptor stimulation (1,9,10,18,23,38).…”
Section: Discussionsupporting
confidence: 89%
“…Five subtypes of muscarinic receptors (M 1 , M 2 , M 3 , M 4 , M 5 ) have been pharmacologically described and molecularly identified (8). Although M 2 receptors outnumber M 3 receptors within smooth muscle, pharmacological studies have indicated that M 3 receptor signaling is responsible for the majority of muscarinic agonist-induced smooth muscle contraction of the lower urogenital tract including the bladder (2) and uterus (1,10,23). Recent studies with M 3 receptor knockout mice have provided further evidence that the M 3 receptor plays the predominant role in mediating smooth muscle contraction (25).…”
mentioning
confidence: 98%
“…For example, the vas deferens (38), prostate gland (39), and corpus cavernosum of penis (40) express mAChRs of the M 3 profile. In addition, M 3 receptors are responsible for uterine smooth muscle contraction (41). However, our result of crosses between homozygous mice suggests that M 3 receptors are dispensable for the normal reproduction of the mouse.…”
Section: Discussioncontrasting
confidence: 46%
“…Uterus contraction in response to acetylcholine or in response to stimulation of cholinergic neurons has been observed in several mammals, including rats (17), pigs (18,19), and humans (20). This effect is mediated by interaction of acetylcholine with muscarinic receptors (4).…”
mentioning
confidence: 97%
“…Leiber et al (22) studied the effects of different muscarinic-receptor antagonists on carbachol-induced contractions and measured accumulation of inositol phosphates and inhibition of cyclic adenosine monophosphate production in the guinea pig uterus. In rat uterus membranes, M2 and M3 muscarinic receptors have been detected using radioligand-binding studies (17). In the porcine uterus, the presence of M3 but not M2 muscarinic receptors has been revealed by functional and radioligand-binding studies (18).…”
mentioning
confidence: 99%